Genome- and transcriptome-assisted development of nuclear insertion/deletion markers for Calanus species (Copepoda: Calanoida) identification - Smolina, Irina; Kollias, S.; Poortvliet, M.; Nielsen, Torkel Gissel; Lindeque, P.; Castellani, C.; Møller, E. F.; Blanco-Bercial, L.; Hoarau, G. (Molecular Ecology Resources, 2014)
Copepods of the genus Calanus are key zooplankton species in temperate to arctic marine ecosystems. Despite their ecological importance, species identification remains challenging. Furthermore, the recent report of hybrids among Calanus species highlights the need for diagnostic nuclear markers to efficiently identify parental species and hybrids. Using next-generation sequencing analysis of both the genome and transcriptome from two sibling species, Calanus finmarchicus and Calanus glacialis , we developed a panel of 12 nuclear insertion/deletion markers. All the markers showed species-specific amplicon length. Furthermore, most of the markers were successfully amplified in other Calanus species, allowing the molecular identification of Calanus helgolandicus , Calanus hyperboreus and Calanus marshallae .